(untitled) (Eurasian Research Bulletin, 2022)
This article is devoted to the topical issue of improving the fight against corruption in the education system of Uzbekistan. The article’s aim is to analyze the experience accumulated by Finland and Denmark in the fight against corruption in the education system in order to study the possibilities of applying the most successful practices of these European states in Uzbekistan. The research methods were the following: analysis of scientific literature and legal acts, comparative legal analysis, induction, deduction and forecasting. The article’s author comes to the conclusion that, by analogy with Finland and Denmark, it would be useful for Uzbekistan to reduce the size of the apparatus of the Ministry of Education, optimize its work, develop and implement an ethical code for workers in this area, conduct more public discussions on this topic, jointly with the AntiCorruption Agency to develop and implement anti-corruption education programs. It would also be useful for Uzbekistan to improve its anti-corruption legislation in accordance with the Council of Europe Criminal Law Convention on Corruption and its additional protocol, it should provide funding for all types of educational institutions in the state budget through the provision of social grants with a strict system of control over spending budget funds exclusively for development these institutions